The world as witty agent—Donna Haraway on the object of knowledge - Trächtler, Jasmin (Frontiers in Psychology, 2024)
In her essay “Situated Knowledges,” the biologist and philosopher of science Donna Haraway tackles the question of scientific objectivity from a feminist perspective and opts for a ‘re-vision’ of science that overcomes the traditional dualisms of epistemic subject and object as well as of nature and culture (science). Beyond scientific realism and radical social constructivism, Haraway understands ‘nature’ or ‘world’ neither as a passive resource nor as a human product of imagination. Rather, she argues, the world is to be understood as a ‘witty agent’ that has its own efficacy and historicity in the production of knowledge. Instead of epistemic reification, possession, and appropriation of ‘nature’, knowledge production should be understood as a conversation between material-semiotic actors, human, and non-human, from which none of the actors leaves as they entered. In this study, I want to explore what it means to conceive of nature or world in knowledge processes as a “witty agent” and how exactly one is to imagine this form of non-human agency. To this end, I will first explain Haraway’s re-vision of “nature” beyond scientific realism and radical social constructivism (sect. 2). From this, I will discuss her underlying conception of agency (sect. 3). This involves first, a reconception of the traditional relation between epistemic subject and object as dynamic and situational relation (sect. 3.1). Second, Haraway characterizes the world’s epistemic agency in more positive terms by using the ‘trickster’ figure as it appears in Southwest Native American representations in the form of a Coyote (sect. 3.2). Finally, I will come back to Haraway’s initial question of an objective scientific approach to the world, which for her consists in a power-charged social relation of conversations with the world. I will conclude with a critical reflection of what Haraway’s conception of the world as an agent means for scientific practice and its engagement with objects of knowledge.